(3MGTjI Ydi GdHgGFjIs - (3YeQ Hf CMeO GdTgjQ HGdeBJi hGdMdis; (3HgGA GdOjf eMeO Hf MSjf GdMGQKj GdgeOGfj GdTjYj GdYGedj,J (B1031 (3g` s
(3ChdgG (B:s
(3jGef YLR Yf LejY JVGYa fYeg CeG HYO ajbhd YeQ Hf CMeO JYdjbGJ Ydi GdehGVY GdeTcdI hJfHjgGJ Ydi QehR dGeHGMK GdeaUdI ai GdQSGdI GdHgGFjI s
(3BNQgG (B:s
(3heYdhe Cf GdNGQL ef GdeGA NeSI aeLehY EKfi YTQ PQGYkG hfUa JeJ GdMGTjI GdhGbaI Ydi GdHgGFjI GdefShHI Edi GHf eGFi GdTgjQ HGHf GdMdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B102s
Keywords: (3GdeLGejYs